From Early Tang Court Debates to China's Peaceful Rise - Assandri, Friederike; Martins, Dora; Assandri, Friederike; Martins, Dora (Amsterdam University Press, 2009)
This volume presents new topics from Chinese history of the last 1400 years from a broad range of fields such as politics, religion, society, economy and culture. The refreshing eight articles give new insights on events as different as the inter-religious court debates of the Tang, the Jiaqing reform of the Qing, the China display on the Chicago World Fair in 1893, Christianity and state-building in Chaozhou, the Taiwan salt trade, Chinese indentured labour in World War I in France, China's rise and current internet regulation. This book highlights the complexity of multi-level interaction of different agents in the center and periphery of China, inside and outside China, contributing to intellectual debates, political and social dynamics, economy structure, modernization, identity building and interaction with the outside.
Dit boek biedt een verfrissende kijk op 1400 jaar Chinese geschiedenis. In acht artikelen worden politieke, religieuze, maatschappelijke economische en culturele geschiedenis tegen het licht gehouden. Uiteenlopende ontwikkelingen komen aan bod, van de interreligieuze rechtbankdebatten van de Tang-dynastie, de Jiaging reformatie van de Qing-dynastie tot China's opkomst en de huidige internetgeneratie.
English
Keywords: History; Politics & government; culture and history; public administration; bestuurskunde; cultuur and geschiedenis; geschiedenis; history, geography, and auxiliary disciplines